An overview of the global statistics on lightning fatalities - Ab Kadir, Mohd Zainal Abidin; Cooper, Mary Ann; Gomes, Chandima (IEEE, 2010)
Lightning is a major cause of weather related mortality around the world. In the United States, lightning typically kills more people in a year than any other storm disaster except floods. Due to persistent lightning safety efforts and an annual National Lightning Safety Awareness Week campaign, US lightning deaths have decreased to an average of about 50 per year in the past decade. Good statistics about death and injuries around the world are just beginning to be collected. This paper presents an update and overview of the global statistics and trends on lightning fatalities which include the gender, activity, time of event and number of casualties. In addition, meteorological info will also be considered in relation to the lightning activity and fatalities.